One new species of the genus Xiphidiopsis Redtenbacher, 1891 (Orthoptera: Tettigoniidae: Meconematinae) from Sichuan, China - Zhou, Tinghong; Wang, Haijian; Shi, Fuming (Zootaxa, 2025)
The paper describes one new species from Sichuan, China, i.e. Xiphidiopsis (Xiphidiopsis) brachysis sp. nov., with a photograph of Xiphidiopsis appendiculata Tinkham, 1944 from China (Sichuan, Guizhou and Hunan). The specimens examined are deposited in the Museum of Hebei University, Baoding, China.